2022
DOI: 10.1101/gad.349488.122
|View full text |Cite
|
Sign up to set email alerts
|

The SpoVA membrane complex is required for dipicolinic acid import during sporulation and export during germination

Abstract: In response to starvation, endospore-forming bacteria differentiate into stress-resistant spores that can remain dormant for years yet rapidly germinate and resume growth in response to nutrients. The small molecule dipicolinic acid (DPA) plays a central role in both the stress resistance of the dormant spore and its exit from dormancy during germination. The spoVA locus is required for DPA import during sporulation and has been implicated in its export during germination, but the molecular bases are unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 48 publications
2
44
0
Order By: Relevance
“…It was also indicated that some of DPA's antioxidant effects were caused by the formation of a chelation complex with copper. That previous report, together with the high occurrence of DPA in Bacillus species, 41,42 suggested that DPA could be one of the metabolites involved in the antioxidant effects produced by Bacillus species 43–45 . For this reason, the antioxidant activity of DPA was screened in this study to reveal new insights into the metabolites that may be involved in Bacillus ‐induced defense responses.…”
Section: Discussionmentioning
confidence: 95%
“…It was also indicated that some of DPA's antioxidant effects were caused by the formation of a chelation complex with copper. That previous report, together with the high occurrence of DPA in Bacillus species, 41,42 suggested that DPA could be one of the metabolites involved in the antioxidant effects produced by Bacillus species 43–45 . For this reason, the antioxidant activity of DPA was screened in this study to reveal new insights into the metabolites that may be involved in Bacillus ‐induced defense responses.…”
Section: Discussionmentioning
confidence: 95%
“…DpaAB encodes the enzyme complex that synthesizes CaDPA (Fig 1A, (35,36)), while SpoVV and SpoVAC are critical in B. subtilis for transporting CaDPA across the outer and then inner forespore membranes, respectively (37,38) (Fig 1A). SpoVV function was first established in B. subtilis (37), whereas SpoVAC has been shown to transport CaDPA into the spore core in several spore-formers, including C. difficile (32,35,(39)(40)(41)(42)(43). CD3298 may act as an accessory protein for the SpoVV or the SpoVAC transporter, although CD3298 lacks a signal sequence (( 23 difficile.…”
Section: Phenotypic Characterization Of Cadpa Mutant Sporesmentioning
confidence: 99%
“…DpaAB is the enzymatic complex that synthesizes DPA, which complexes with Ca 2+ ions before it is transported across the outer (OM) and inner forespore membranes (IM). SpoVV is the putative CaDPA transporter in the OM (37), while SpoVAC is the CaDPA transporter located in the IM (43). CD3298 (orange circle) is a putative ATP-binding protein previously shown to be important for CaDPA transport in C. difficile (23), but it is unclear whether it associates with SpoVV or SpoVAC.…”
Section: Phenotypic Characterization Of Cadpa Mutant Sporesmentioning
confidence: 99%
“…Although the profile of the germination process, especially physiological events, is relatively clear, signal transduction and the underlying mechanisms are obscure. Recently, the application of AlphaFold 2 to identify the spatial structure of GRs or Ca‐DPA channel proteins revealed their possible mode of action during germination (Amon et al., 2022; Artzi et al., 2021; Y. Gao, Barajas‐Ornelas, et al., 2022), and the finding that potassium ion release integrates germination signals sheds light on the mystery process of signal transduction following GRs activation (Kikuchi et al., 2022). Moreover, the occurrence of macromolecule synthesis during germination (Sinai & Ben‐Yehuda, 2016; Sinai et al., 2015; Zhou et al., 2022, 2019) and the proposed high correlation between ATP levels and spore germination capability (Rao et al., 2022) have been demonstrated, but these concepts are controversial (Boone & Driks, 2016; Korza et al., 2017, 2023, 2016; Swarge, Abhyankar, et al., 2020; Swarge, Nafid, et al., 2020).…”
Section: Introductionmentioning
confidence: 99%